Identification of MSXl gene mutation in Kelantanese patients with various types of non-syndromic cleft lip and palate - Nurhanini, Abd Rahman
Orofacial cleft are congenital structural abnonnalities of the lip and/or palate that affect between 1 in 2000 and 1 in 500 live births worldwide. In Kelantan, it affects 1 in 600 live births. MSXl gene is one of the target genes which produce the most consistent result with the incidence of non-syndromic cleft lip and/or palate. This gene is located in chromosome 4 at short ann, p16.3-p16.1. It has two exons that code for a homeodomain-containing protein of 297 amino acids and one intron. Thirty-five patients with non-syndromic cleft lips and lor palate and 35 control blood samples were included in this study. The mutation of MSXl gene has successfully been detected in the intron of this gene using MSXI-CA. This primer amplified nine CA repeats and produced 169 base pair using polymerase chain reaction (PCR). After amplification, the product was electrophorosed to detect the mutation by getting two bands. This showed the CA repeat was expanded to more or less than nine repeats for mutated gene. Out of thirty-five patients tested, five (2%) showed variation from the others while seven (31.4%) showed variation in particular locus from control samples. There was no association between MSXl gene mutation and clefting (P=O.275). But the sample size is rather limited. Larger sample size is needed for future studies.